(untitled) (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
This paper presents a multilayered framework that explores the interdependent dynamics of harassment, victim resilience, and systemic judicial bias. Drawing on Stratad Theory’s principles of precise conceptualisation and functional naming, this study develops three interconnected theories: Harassing, Gentling, and Injusticing. Each theory examines a distinct dimension of the harassment experience, from the perpetrator’s tactics of intimidation to the victim’s resilient sociostructural responses and, ultimately, the legal system’s role in reinforcing harm through procedural bias and neglect. Synthesising these dimensions, Injusticing illustrates how harassment is perpetuated within a legal environment that often favours perpetrators and disadvantages victims. The paper highlights key terminology, including mindsetting, wholehearting, and negligencing, providing a practical framework for understanding and addressing these issues. This theory offers valuable insights for legal practitioners, policymakers, social workers, and support networks, emphasising the need for judicial reform and empowering individuals to confront and mitigate the psychosocial and legal challenges associated with harassment.